¿De qué manera podrían las empresas del segmento B2B incrementar la efectividad de sus acciones de comunicación y marketing? - Barco Chrem, Iván Eduardo Joaquín (2021)
Should business and marketing be segmented into B2B or B2C? This question is key because it will support the way a company will analyze its environment and design its marketing strategies, if it even uses one. This being one of the problems that precisely exist in terms of marketing that focuses on businesses that seek to build good working relationships with other businesses, the lack of adequate strategies for a client who thinks differently from a final consumer. Probably because marketing traditionally directs its approaches towards end customers and B2C environments to generate its strategies, which may not be suitable for an industrial customer. We will analyze B2B marketing in depth, investigating how to properly interact with clients in business-to-business environments, investigating the appropriate way to understand this particular segment and we will finally seek to offer the best strategies to successfully manage long-term relationships with clients of this type.